Contrast-Induced Nephropathy in patients submitted to percutaneous coronary intervention: an integrative review - Matheus Santos Moitinho; Eduesley Santana Santos; Adriano Mendes Caixeta; Angélica Gonçalves da Silva Belasco; Dulce Aparecida Barbosa; Cassiane Dezoti da Fonseca
ABSTRACT Objective: to demonstrate scientific evidence on incidence and factors associated with contrast-induced nephropathy in patients undergoing percutaneous coronary intervention. Methods: an integrative review carried out in the VHL, PubMed, VHL Regional Portal and SciELO databases, of articles published between 2014 and 2019. Results: the sample consisted of five original articles, two cohorts, two control cases and a clinical trial. The incidence of contrast-induced nephropathy ranged from 6% to 24%. It stands out among patients with advanced age, male gender, diabetes mellitus, systemic arterial hypertension, volume of contrast infused and osmolarity. Intravenous hydration, sodium bicarbonate, ascorbic acid and statin were important prophylactic agents. Conclusion: this study envisioned the main risk factors for contrast-induced nephropathy in patients undergoing percutaneous coronary intervention and elucidated preventive measures that guide multidisciplinary health care aiming at a quality and safe care.